2021
DOI: 10.1002/adsu.202100128
|View full text |Cite
|
Sign up to set email alerts
|

Responsive Bio‐Composites from Magnesium Carbonate Filled Polycaprolactone and Curcumin‐Functionalized Cellulose Fibers

Abstract: non-toxicity, low-density, biocompatibility properties, and low cost. [1][2][3][4][5] The main drawback associated with the use of cellulose in specific composites-related applications is its water sensitivity and ability to uptake significant amounts of moisture. [6][7][8] On the other hand, cellulose fibers have very good mechanical properties, and because of this, they have been employed to reinforce many petroleum polyolefins or bio-based resins. [9][10][11] Advances in the development of cellulose nanofib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 108 publications
(125 reference statements)
0
15
0
Order By: Relevance
“…Recently, Quilez-Molina et al (2021) [ 153 ] developed curcumin-functionalized cellulose–magnesium and carbonate–PCL hybrid biocomposites. Magnesium carbonate (MgCO 3 ) was used as a food additive.…”
Section: Polycaprolactone-based Hydrid Biocompositesmentioning
confidence: 99%
“…Recently, Quilez-Molina et al (2021) [ 153 ] developed curcumin-functionalized cellulose–magnesium and carbonate–PCL hybrid biocomposites. Magnesium carbonate (MgCO 3 ) was used as a food additive.…”
Section: Polycaprolactone-based Hydrid Biocompositesmentioning
confidence: 99%
“…The color changes of the porous material can be visually perceived even by inexperienced users, as demonstrated by CIELAB color space analysis. Above all, results showed that the porous fiber mats present an increased sensitivity compared to their non-porous equivalents and, consequently, to the vast majority of the up to date colorimetric indicators, which have mostly the form of films , or pore-less fibers. ,, The presented study highlights the importance of the high porosity for an efficient and rapid visual inspection of the alkaline environment, necessary for various applications, such as intelligent food packaging, environmental protection, and biomedicine.…”
Section: Discussionmentioning
confidence: 65%
“…The presented study reveals the importance of the highly porous structure for an effective and real-time colorimetric indication of alkaline vapors. Compared to the majority of the studies presented so far on colorimetric indicators containing natural molecules ,, such as curcumin, ,, ,,, which test the efficiency of the material to change color in the presence of buffer solutions, ,, acidic or alkaline vapors, ,,,, and/or acidic or alkaline semisolid media without proper investigation of different concentrations, or with no precise evaluation of the kinetics of the color change and reusability, , this work offers a comprehensive view of the overall performance of the system in terms of responsivity, sensitivity, and reusability. Compared to the already explored curcumin-based films , , and fibrous mats, ,, but also compared to other types of colorimetric indicators, , PCLCU1 mats present faster color change response and higher sensitivity.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations